Penerapan Good Corporate Goverence (GCG) Di Bank Sumut Syariah - Azizahsekarningrum; Jannah, Nurul (Balance : Jurnal Akuntansi dan Manajemen, 2022)
This paper discusses the application of good corporation governance in Islamic banks in North Sumatra. GCG is a process or structure to control and direct the company. Based on this understanding, GCG basically discusses how a company is managed and directed and coordinated properly. This type of research uses qualitative descriptive, namely by paying attention and describing the data from the results obtained to be described in order to get results that are supported by theory. The implementation of the implementation of good corporation governance at the Islamic Bank of North Sumatra has become a basic need that has become a necessity so that the corporate governance system at the Islamic Bank of North Sumatra runs well. If the good cooperation governance mechanism is carried out properly, it will be an added value to the Islamic bank of North Sumatra because good corporation governance can overcome if there is a violation such as providing maximum credit limits, low risk management practices, and the absence of transparent transactions between customers and shareholders in operational activities.